2004
DOI: 10.1111/j.1540-4609.2005.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to the Success of Undergraduate Business Students in Management Science Courses

Abstract: The introductory management science (MS) course has historically been recognized as one of the most difficult core courses in the business school curriculum. This study uses multiple regression to examine the factors that contribute to the success of undergraduate business students in an MS course, based on data gathered from the college transcripts and academic files of 310 students. The results suggest that the strongest predictive variable is a student's college grade point average, indicating that overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 21 publications
9
43
4
Order By: Relevance
“…For example, Brookshire and colleagues found that GPA was the only variable that was positively correlated with grades in a management science course (Brookshire and Palocsay, 2005). These results support the commonsense idea that a student's record of overall academic performance as measured by grades would be relatively consistent.…”
Section: Impact Of Organic Chemistry Prerequisitesupporting
confidence: 72%
“…For example, Brookshire and colleagues found that GPA was the only variable that was positively correlated with grades in a management science course (Brookshire and Palocsay, 2005). These results support the commonsense idea that a student's record of overall academic performance as measured by grades would be relatively consistent.…”
Section: Impact Of Organic Chemistry Prerequisitesupporting
confidence: 72%
“…Studies that focus on the intellectual variables of business majors include Brookshire and Palocsay (2005) and Smith and Schumacher (2006). Both studies singled out the effects of intellectual variables such as SAT scores, percentile rank in high school graduating class, scores on college mathematics placement exams, grades in specific general education courses, and college grade point averages on the success of students in an introductory management science course and in an actuarial studies programme, respectively.The conclusion from theses studies is that intellectual variables are good predictors of academic success for college students in general and business school students in particular.…”
Section: Introductionmentioning
confidence: 99%
“…A number of early studies examined the importance of traditional variables in predicting academic performance such as high school GPA, SAT score, high school class rank and GMAT [1], [3], [9], [10], [14], [15], and [16]. Similarly, there are a number of up-to-date research that have produced evidence of an association between personality, conscientiousness, openness to experience, emotional stability, agreeableness and academic success [6], [10], [12], and [15].…”
Section: Review Of Literaturementioning
confidence: 99%